2017
DOI: 10.1186/s12891-017-1791-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of 1α-hydroxylase and vitamin D receptor in human articular chondrocytes

Abstract: BackgroundThe aim was to investigate whether resident chondrocytes in human articular cartilage and in subculture express vitamin D receptor (VDR) and the enzyme that hydroxylates the prohormone 25(OH)D3 to the active hormone 1α,25(OH)2D3, namely 1α-hydroxylase (CYP27B1). Any putative effects of vitamin D on chondrocytes were also explored.MethodsCartilage from human osteoarthritic knee joints, cultured chondrocytes and cells grown in 3D spheroids were examined for the expression of VDR and 1α-hydroxylase by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Chondrocytes can produce vitamin D metabolites under the regulation of growth factors and hormones, and these metabolites play an important role in the regulation of matrix vesicles ( Assmusen et al., 2017 ). Vitamin D3 has been suggested to dampen OA, which may indicate a relationship between vitamin D3 and OA ( Hansen et al., 2017 ). We observed that vitamin D3 downregulates TLR4 and decreases TNF-α and IL-6 release ( Jo et al., 2015 ; Adamczak, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes can produce vitamin D metabolites under the regulation of growth factors and hormones, and these metabolites play an important role in the regulation of matrix vesicles ( Assmusen et al., 2017 ). Vitamin D3 has been suggested to dampen OA, which may indicate a relationship between vitamin D3 and OA ( Hansen et al., 2017 ). We observed that vitamin D3 downregulates TLR4 and decreases TNF-α and IL-6 release ( Jo et al., 2015 ; Adamczak, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has various effects on different tissues and cells [27][28][29][30][31][32][33]. Vitamin D deficiency is reported to result in abnormal calcium, phosphorus and bone metabolism [27].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are successfully isolated and expanded in vitro from numerous tissues sources. MSCs represent a defined population of multipotent progenitor cells residing in the perivascular niche of nearly all human tissues, although different views exist (Crisan et al, 2008;Guimaraes-Camboa et al, 2017). MSC differentiation capacity and immunomodulatory properties are demonstrated in vitro, irrespective of tissue sources (Ghannam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of cartilage repair and OA, the fate of implanted cells during biological repair procedures and their contribution to rebuilding the damaged tissue is mostly unknown. Previous studies in animals suggest that most of the repaired tissue is composed of cells of unknown origin migrating to the lesion (Dell'Accio et al, 2003;Grande et al, 1989). A recent human clinical trial has concluded that allogeneic bone marrow MSCs function as a source of stimulatory and trophic factors, which orchestrate tissue repair rather than differentiating into the host tissue (de Windt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%